Experimental investigation of local scour around cylindrical pile foundations in a double-layered sediment under current flow. (1st May 2022) - Wang, Chen; Yuan, Ye; Liang, Fayun; Tao, Junliang
Abstract: Scour is a natural phenomenon that occurs when the soil around piles erodes, and it is significantly affected by the characteristics of the seabed or riverbed materials, the nearby submerged obstructions, and the water flowing past. Water–sediment interaction is a critical process that may lead to the loss of bed materials and influence the mechanical behavior of foundations. Exploring the scour mechanism is essential for predicting scour depth and designing appropriate countermeasures, especially those that consider essential concepts in geomechanics as well as complex geological conditions. This study presents a series of tests on piles embedded in single- and double-layered sediments that are composed of coarse, medium, and fine sands. The results show that the properties of the overlying soil layer govern the initiation of erosion and the final scour range, while those of the underlying layer determine the final scour depth. As the exposed sediments and their scour resistance at the water–soil interface change during the scour, predictions of scour depth that are merely based on the properties of the surface layer of the sediment may not be accurate. Based on the experimental results, an innovative predictive framework of scour depth was proposed that considers sediments with two layers. Highlights: Layered soils are widely distributed, and the influence of changing soil characteristics needs to be considered. The properties of the overlying soil layer govern the initiation of erosion and the final scour range. The properties and thickness of the underlying layer determine the final scour depth. A predictive framework of scour depth was proposed considering double-layered soil conditions.